A study of organizational change and supply chain management practices: an empirical analysis on SME sector in Malaysia - Kong, Chan Leong; Jaharuddin, Nor Siah; Yee, Choy Leong (Centre for Promoting Ideas, 2020)
The reason for this analysis is to introduce the correlation between organizational change and supply chain management (SCM) practices and supply chain responsiveness (SCR), and explores its relationship with upper hand. The data assortment instrument utilized was a survey which was administrated to an absolute sample of 200 managers from SMEs part in Malaysia's. The reaction rate was 70% while 60% was usable questionnaires. Sample determination depended on convenience sampling. The researches included statistical descriptive strategies, for instance theliability and validity tests and various regressions. The outcomes demonstrated that SCM practices are identified with SCR. The outcome likewise recommended that SCR is identified with upper hand take part.